2014
DOI: 10.1038/cr.2014.10
|View full text |Cite|
|
Sign up to set email alerts
|

VGLL4 functions as a new tumor suppressor in lung cancer by negatively regulating the YAP-TEAD transcriptional complex

Abstract: Lung cancer is one of the most devastating diseases worldwide with high incidence and mortality. Hippo (Hpo) pathway is a conserved regulator of organ size in both Drosophila and mammals. Emerging evidence has suggested the significance of Hpo pathway in cancer development. In this study, we identify VGLL4 as a novel tumor suppressor in lung carcinogenesis through negatively regulating the formation of YAP-TEAD complex, the core component of Hpo pathway. Our data show that VGLL4 is frequently observed to be lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
226
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(242 citation statements)
references
References 49 publications
3
226
1
Order By: Relevance
“…Through a TEAD4-responsive luciferase report, we found that overexpression of Yap significantly enhanced the activity of luciferase reporter (Fig. 3I), as described elsewhere (41). However, ectopic expression of RARg led to a dramatic decrease of Yap-induced luciferase activity (Fig.…”
Section: Rarg Inhibits Yap-tead Transcriptional Activity and Yap Targmentioning
confidence: 78%
See 1 more Smart Citation
“…Through a TEAD4-responsive luciferase report, we found that overexpression of Yap significantly enhanced the activity of luciferase reporter (Fig. 3I), as described elsewhere (41). However, ectopic expression of RARg led to a dramatic decrease of Yap-induced luciferase activity (Fig.…”
Section: Rarg Inhibits Yap-tead Transcriptional Activity and Yap Targmentioning
confidence: 78%
“…Yap facilitates regulation of downstream target gene expression by directly binding to the transcription factor TEADs (40,41). Through a TEAD4-responsive luciferase report, we found that overexpression of Yap significantly enhanced the activity of luciferase reporter (Fig.…”
Section: Rarg Inhibits Yap-tead Transcriptional Activity and Yap Targmentioning
confidence: 89%
“…Suppression of ⌬Np63-Two recent studies suggest that TEAD or its Drosophila homolog Scallop can suppress cellular gene transcription through interaction with transcription cofactor VGLL4 or Tgi, respectively (39,40). However, VGLL4 knockdown in MCF10A cells could not block TAZ-induced suppression of ⌬Np63 (Fig.…”
Section: Modulation Of Deacetylation Is Critical For Taz-tead-inducedmentioning
confidence: 94%
“…VGLL4 acts as a tumor suppressor in both lung and gastric cancers by repressing YAP-TEAD activity. In addition, a peptide mimicking VGLL4 function acts as a YAP antagonist and shows prominent anti-cancer activity in gastric cancer models [127,128].…”
Section: Teads Are Major Transcription Factor Partners Of Yapmentioning
confidence: 99%